2014
DOI: 10.3389/fnagi.2014.00073
|View full text |Cite
|
Sign up to set email alerts
|

Age-related neurochemical changes in the rhesus macaque inferior colliculus

Abstract: Age-related hearing loss (ARHL) is marked by audiometric hearing deficits that propagate along the auditory pathway. Neurochemical changes as a function of aging have also been identified in neurons along the auditory pathway in both rodents and carnivores, however, very little is known about how these neurochemicals change in the non-human primate. To examine how these compensatory neurochemical changes relate to normal aging and audiometric sensitivity along the auditory pathway, we collected auditory brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 67 publications
(140 reference statements)
0
26
0
Order By: Relevance
“…In this case, the medial area labeled as CNIC appears to occupy what is generally considered DC in most anatomical divisions in other species (Andersen, Snyder and Merzenich 1980; Herbert, Aschoff and Ostwald 1991; Saldaña, Feliciano and Mugnaini 1996; Winer et al 1998). However, modern studies in the same species appear to roughly confirm Fitzpatrick and Imig's subdivisions (Hackett, Takahata and Balaram 2011; Engle et al 2014). Irrespective of differences in definitions of subdivisions, granting the CNIC space medially it is still clear that most of the projections are to the CNIC and not to the DC and LC, curiously, which are most prevalent in other species (Andersen, Snyder and Merzenich 1980; Herbert, Aschoff and Ostwald 1991; Saldaña, Feliciano and Mugnaini 1996; Winer et al 1998).…”
Section: Anatomical Considerationsmentioning
confidence: 61%
See 1 more Smart Citation
“…In this case, the medial area labeled as CNIC appears to occupy what is generally considered DC in most anatomical divisions in other species (Andersen, Snyder and Merzenich 1980; Herbert, Aschoff and Ostwald 1991; Saldaña, Feliciano and Mugnaini 1996; Winer et al 1998). However, modern studies in the same species appear to roughly confirm Fitzpatrick and Imig's subdivisions (Hackett, Takahata and Balaram 2011; Engle et al 2014). Irrespective of differences in definitions of subdivisions, granting the CNIC space medially it is still clear that most of the projections are to the CNIC and not to the DC and LC, curiously, which are most prevalent in other species (Andersen, Snyder and Merzenich 1980; Herbert, Aschoff and Ostwald 1991; Saldaña, Feliciano and Mugnaini 1996; Winer et al 1998).…”
Section: Anatomical Considerationsmentioning
confidence: 61%
“…Modules in DC, layer 2 of the LC and in the rostral pole were distinguished by a population of GAD-positive somatic staining and a much higher local concentration of terminals than in non-modular parts of these nuclei (Chernock, Larue and Winer 2004). Other studies have shown the presence of such modularity and/or patchiness in the monkey, rat and mouse, though not always commented upon in the text (Paxinos, Watson and Emson 1980; Herbert, Aschoff and Ostwald 1991; Ono, Yanagawa and Koyano 2005; Ito, Bishop and Oliver 2009; Engle et al 2014), and some unresolved questions remain. For example, Herbert et al (1991) appear to show NADPH-d staining in the LC that is nonmodular and avoids layer 2, while other studies in rat (e.g.…”
Section: Molecular and Circuit-level Considerationsmentioning
confidence: 94%
“…Beyond the cochlea, animal and human data demonstrate age-related changes in function in spiral ganglion neurons [25], cochlear nuclei [26], the superior olivary complex, and other midbrain structures up through the inferior colliculus [27,28]. Age-related changes in the auditory brainstem can yield altered temporal processing ability [29,30], which may be reflected in reduced ability in tasks such as detecting a brief temporal gap in a continuous tone [31].…”
Section: Changes To the Auditory System In Adult Agingmentioning
confidence: 99%
“…Whereas the present and previous ABR studies showed a decrease in ABR amplitudes among geriatric monkeys, PV-or NADPHd-stained cells within the central auditory system instead increased with the same ABR parameter in aged subjects. Although the exact nature of the increased PV/ NADPHd-positive cells within the central auditory system is still unclear, the phenomenon is proposed as a compensation to enhance the efficacy of inhibitory mechanisms during normal aging (Caspary et al 2008;Engle et al 2014).…”
Section: Comments On Uses Of Abrs To Measure Hearing Sensitivity In Omentioning
confidence: 99%